THE EFFECT OF GREEN SUPPLY CHAIN MANAGEMENT PRACTICES TOWARDS CONSUMER PURCHASE INTENTION AND WILLINGNESS TO PAY PREMIUM: MEDIATION AND MODERATION ANALYSIS - Hadith Fadhillah; Wahyuningsih Santosa; Dorina Widowati; Ratna Darasih (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the effect of green supply chain management practices on consumers' purchase intention and willingness to pay premium using mediation and moderation analysis. This study obtained data by distributing online questionnaires to Generation Z and Millennial consumers who had purchased products from coffee shops that had implemented green supply chain management practices in Jakarta. The sample used in this study consisted of 289 respondents. The data analysis method used was SEM-PLS analysis using SmartPLS software. The results of this study indicate that green supply chain management practices have a positive effect on perceived product performance, willingness to pay premium, and consumer purchase intention. The results also show that perceived product performance mediates purchase intention but does not mediate consumers' willingness to pay more. Consumers' moral orientation towards the environment does not moderate the direct effect of green supply chain management practices on the other three variables.